Analysis of Geothermal Potential Using Gravity Method in Way Ratai Area, Pesawaran Regency, Lampung - Adelia, Putri; -, Suwondo; Martha, Agustya Adi; Franzisca, Tiara Grace (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
Way Ratai, Pesawaran is one of the areas in Lampung that has a surface manifestation, in the form of geothermal potential. Based on data from the Directorate of Geothermal in 2017, Way Ratai has a potential of more than 330 MW with the manifestation of hot springs and hot steam. This study aimed to determine the distribution of subsurface density of Mount Way Ratai, Pesawaran, Lampung region by using ggmplus satellite gravity data. Based on fault analysis method and 2D forward modeling in Oasis Montaj software. The results showed that the geothermal area of Way Ratai identified 2 types of faults, namely reverse faults and normal fault. Based on the results of forward modeling, subsurface density of Way Ratai area, Lampung offering can be identified at a density of 1.2 gr/cc suspected alteration rocks in the form of clay minerals, density of 1.55 gr/cc suspected sand gravel, density of 1.6 gr/cc suspected Tuff rocks, density of 2.3 gr/cc suspected breccia rocks and conglomerates, density 2.6 gr/cc suspected schist and chert, and density 2.99 gr/cc suspected basalt rocks.